Exchange-rate variability and industry trade flows between Malaysia and Japan - Aftab, M.; Syed, K.B.S.; Ahmad, Rubi; Ismail, Izlin (Taylor & Francis, 2016)
This research investigates the exchange-rate risk sensitivity of Malaysian bilateral trade flows with its important trading partner, Japan. To this end, bounds testing approach to co-integration is applied using industry level data over the monthly period 2000–2013. Findings suggest that above the one-third of the total co-integrated export (43.86%) and import (34.54%), industries experiences the ringgit/yen variability effect in the short run. However, this effect sustains in relatively less number of export (14.03%) and import (32.73%) industries in the long run. It is interesting to note that exchange-rate risk boosts trade flows in the majority of these affected industries.